2020
DOI: 10.1039/d0sc00086h
|View full text |Cite
|
Sign up to set email alerts
|

Engineering base-excised aptamers for highly specific recognition of adenosine

Abstract: The DNA aptamer for adenosine and ATP has been used as a model system for developing analytical biosensors. For practical reasons, it is important to distinguish adenosine from ATP, although this has yet to be achieved despite extensive efforts made on selection of new aptamers. We herein report a strategy of excising an adenine nucleotide from the backbone of a one-site adenosine aptamer, and the adenineexcised aptamer allowed highly specific binding of adenosine. Cognate analytes including AMP, ATP, guanosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…This implies that ATP-33 can bind to all adenosine analogs but not nucleotide trisphosphates in general, which reflects the binding profile of this aptamer as reported by originally by Huizenga and Szostak ( 35 ). Moreover, aptamer digestion in the presence of each ligand resulted in a different amount of retained product and the level of enzymatic inhibition for each analog coincided with their previously reported cross-reactivity ( 17 , 36 , 37 ). For example, more 28-nt product (as well as undigested aptamer) was retained for ADP and adenosine relative to ATP and AMP (Figure 1D ), which implies that the aptamer binds more strongly to the former pair.…”
Section: Resultssupporting
confidence: 85%
“…This implies that ATP-33 can bind to all adenosine analogs but not nucleotide trisphosphates in general, which reflects the binding profile of this aptamer as reported by originally by Huizenga and Szostak ( 35 ). Moreover, aptamer digestion in the presence of each ligand resulted in a different amount of retained product and the level of enzymatic inhibition for each analog coincided with their previously reported cross-reactivity ( 17 , 36 , 37 ). For example, more 28-nt product (as well as undigested aptamer) was retained for ADP and adenosine relative to ATP and AMP (Figure 1D ), which implies that the aptamer binds more strongly to the former pair.…”
Section: Resultssupporting
confidence: 85%
“…It is known that G8, G9, G18, G19, and A10 are all highly conserved, and any mutation to them can abolish aptamer binding [8a] . In our previous study we found that the A10‐excised aptamer can specifically recognize adenosine [12] . Taking together the observations of the G19‐excised aptamer here, and the two Na + aptamers ΔG16 and ΔA10, highly conserved purines are more likely to be optimal excision sites than nonconserved purines, although not all conserved sites work.…”
Section: Resultsmentioning
confidence: 88%
“…In general, an aptamer should bind its target with a well‐defined three‐dimensional structure and contain guanines that are involved in target binding. We previously excised an adenine from a duplex region, but this did not allow the rebinding of adenosine [12] . Therefore, not all DNA structures can be used for targeted binding of purines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations